2016
DOI: 10.3920/bm2016.0089
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Lactobacillus rhamnosus SP1 normalises skin expression of genes implicated in insulin signalling and improves adult acne

Abstract: Systemic supplementation with probiotics is increasingly being explored as a potential treatment strategy for skin disorders. Because both the gut-skin axis and dysregulation of insulin signalling have been implicated in the pathogenesis of adult acne, we designed the current study to evaluate the effect of supplementation with the probiotic strain Lactobacillus rhamnosus GG (LGG) on skin expression of genes involved in insulin signalling and acne improvement in adult subjects. A pilot, randomized, double-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 30 publications
2
79
0
11
Order By: Relevance
“…These observations raise hope that the right kind of bacteria may have beneficial effects on the skin homoeostasis, skin inflammation, and peripheral tissue responses to perceived stress. Other studies conducted in humans confirmed this hypothesis [76-78]. Thus, probiotics may be efficient in acne and other inflammatory skin diseases such as atopic dermatitis and potentially psoriasis [79-83].…”
Section: Resultssupporting
confidence: 59%
“…These observations raise hope that the right kind of bacteria may have beneficial effects on the skin homoeostasis, skin inflammation, and peripheral tissue responses to perceived stress. Other studies conducted in humans confirmed this hypothesis [76-78]. Thus, probiotics may be efficient in acne and other inflammatory skin diseases such as atopic dermatitis and potentially psoriasis [79-83].…”
Section: Resultssupporting
confidence: 59%
“…Very few controlled studies have investigated the benefit of oral probiotics in the treatment of acne. When compared to the placebo in 20 patients, the probiotic containing Lactobacillus rhamnosus SP1 provided a better clinical outcome according to the investigators . An adjunctive supplementation of lyophilized Lactobacillus acidophilus and Bifidobacterium bifidum adjunctively to standard antibiotics improved acne in 40 patients .…”
Section: Resultsmentioning
confidence: 98%
“…The transcription factor FoxO1 has been related to the response of probiotics in C. elegans oxidative stress, skin acne and alcoholic fatty liver [22,45,46]. Nevertheless, this is the first study linking FoxO1 activation to probiotics response in intestinal mammalian cells.…”
Section: Discussionmentioning
confidence: 87%